Low-anisotropy aluminum-lithium alloy and preparation method and application thereof
By adjusting the element content and rolling process of aluminum-lithium alloy, controlling the second phase precipitation and texture composition, the serious anisotropy of aluminum-lithium alloy is solved, and the comprehensive mechanics of low density, high strength and low anisotropy are achieved. Performance improvement.
Patent Information
- Application Number
- CN202310939509.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-14
AI Technical Summary
The anisotropy of existing aluminum-lithium alloys is relatively serious, which limits the matching of its application range and aerospace field.
By reasonably adjusting the alloy elements and content, the precipitation of the second phase in the matrix is mainly to reduce the anisotropy δ′ phase and Al3 (Er, Zr) composite phase, and to affect the texture composition by changing the rolling process, eliminating the Strong texture, transformed into a brass R-type texture that suppresses alloy anisotropy.
The low density, high specific strength, high toughness and low anisotropy of aluminum-lithium alloy are achieved, which improves the comprehensive mechanical properties of the alloy, reduces the anisotropy and improves the mechanical properties.
Smart Images

Figure CN119433295A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a low-anisotropy aluminum-lithium alloy and a preparation method and application thereof, belonging to the technical field of aluminum-lithium alloy material preparation. Background Art
[0002] Aluminum-lithium alloy has two main advantages: low density and high modulus. It is considered to be the most ideal lightweight and high-strength structural material in the aerospace field in the 21st century. The overall strategy for improving the strength and plasticity of the third-generation aluminum-lithium alloy is to reduce the Li content while further increasing the Cu content. Instead of blindly pursuing lightweighting, the research and development ideas are changed from the perspective of comprehensive performance. The Li content in the aluminum-lithium alloy is reduced to below 2wt.%, and while increasing the Cu content, a variety of micro-alloying elements such as Mg, Zr and Ag are added. The second phase composition and proportion in the aluminum-lithium alloy are regulated by composition design, which improves the mechanical properties of the alloy such as strength and fracture toughness, making it exhibit excellent comprehensive performance.
[0003] T1 phase is one of the main strengthening phases in Al-Li-Cu alloy, belonging to the hexagonal crystal system. T1 phase has different orientation angles and different hindering effects on dislocation movement. When loaded along the rolling direction, the precipitation and distribution of this T1 phase makes the hindering effect on slip the largest, which can cause effective strengthening. The strengthening contribution of T1 phase in the 45° direction is significantly higher than the rolling direction and transverse value, resulting in severe plane anisotropy of aluminum-lithium alloy with T1 phase as the main strengthening phase, and the mechanical properties in the rolling direction, 45° and transverse direction are quite different. δ′ phase has a very small mismatch with the aluminum matrix, so δ′ phase has an excellent coherent relationship with the aluminum matrix and has little effect on anisotropy. In addition, the binding energy of δ′ phase with vacancies is high, and it is very easy to combine with vacancies, so δ′ phase is easy to precipitate from the aluminum matrix. These determine that δ′ phase is the most important precipitation phase in aluminum-lithium alloy and also a strengthening phase. Furthermore, through first-principles density functional theory calculations, the elastic modulus of the δ′ phase can reach up to 158.0 GPa. Therefore, the advantage of high modulus of aluminum-lithium alloy mainly comes from the δ′ phase.
[0004] After aluminum-lithium alloy is rolled, its internal grains will be arranged along certain specific directions to form some regular orientations, which is the preferred orientation of the grains, also known as texture. The existence of texture generally causes serious anisotropy in the material, affecting the performance of the material. Different texture types have a great influence on the mechanical properties of the material, especially on the degree of anisotropy of the material. Under different rolling process conditions, the texture components of the alloy material are different, which makes the degree of anisotropy of the material different.
[0005] In general, the anisotropy of deformed aluminum-lithium alloys is relatively serious, which limits their application scope and their matching with the needs of aerospace engineering. In order to ensure the implementation of major national projects in the field of aerospace, it is urgent to expand the application of lightweight and high-strength aluminum-lithium alloys in aerospace equipment, especially vertical helicopters and heavy-lift launch vehicles. It is of great significance to further improve the comprehensive performance of aluminum-lithium alloys so that they can meet more new needs in the aerospace field and promote the research and development of high-quality aluminum-lithium alloys. Summary of the invention
[0006] In view of the serious anisotropy problem of existing aluminum-lithium alloys, the present invention provides a method for reducing the anisotropy of aluminum-lithium alloys by controlling the precipitation of the second phase through alloying and affecting the texture composition by changing the rolling process, so as to improve the comprehensive mechanical properties of aluminum-lithium alloys.
[0007] The technical solution of the present invention:
[0008] One of the objects of the present invention is to provide an aluminum-lithium alloy with low anisotropy, which is composed of the following components in mass percentage: Li 3%, Cu 1%, Mg 0.4%, Er 0.1%, Zr 0.1%, and the balance is Al.
[0009] It is further defined that the precipitation phase of the aluminum-lithium alloy is mainly δ′ phase and Al3 (Er, Zr) composite phase.
[0010] It is further defined that the aluminum-lithium alloy is obtained by smelting and casting aluminum ingots, Mg, metallic lithium, intermediate alloys Al-50wt.% Cu, Al-10wt.% Er and Al-10wt.% Zr as raw materials to obtain a cast alloy, which is then annealed and plate rolled.
[0011] A second object of the present invention is to provide a method for preparing the above-mentioned low anisotropy aluminum-lithium alloy, the method comprising the following steps:
[0012] (1) melting and casting to obtain a cast AlLiCuMgErZr alloy;
[0013] (2) annealing the cast AlLiCuMgErZr alloy, and then cutting it to obtain an aluminum-lithium alloy plate;
[0014] (3) The aluminum-lithium alloy plate is subjected to multiple cross hot rolling, with the cumulative deformation being greater than 70% and the hot rolling temperature being 450° C. to 550° C.
[0015] Further defined, the specific operation process of (1) is:
[0016] The first step is to melt the aluminum ingot: heat the pit-type resistance furnace with the crucible to 780°C, then put the pure aluminum ingot into the crucible and heat it. After the furnace temperature stabilizes at 780°C, keep it warm for 1 hour to ensure that the pure aluminum ingot is completely melted;
[0017] The second step is to add the master alloy: after the furnace is opened, the slag is firstly removed, and then the prepared Al-50wt.%Cu, Al-10wt.%Er and Al-10wt.%Zr master alloys are put into a graphite crucible, and then a small amount of covering agent is evenly sprinkled on the surface of the melt until the surface of the melt is completely covered; then the furnace temperature is returned to 780°C and stabilized, and then the temperature is kept for 40 minutes to make the master alloy completely melted and fully react with the melt. After the insulation is completed, the melt is refined twice with a refining agent, and the slag is removed; then argon gas is introduced into the melt for 1 minute to remove impurity gases in the melt, and then the slag is removed again and a small amount of covering agent is evenly sprinkled on the surface of the melt. After the complete coverage, the furnace temperature is stabilized at 780°C and the temperature is kept for 5 minutes;
[0018] The third step is to add pure Mg: after the heat preservation is completed, the temperature is lowered to 740°C, and after the temperature is stable, the temperature is kept for 5 minutes; after the heat preservation is completed, the furnace is opened to remove the slag, and then the pure Mg is placed in the graphite crucible, and the surface of the melt is immediately covered with a covering agent, and then after the temperature is stabilized at 740°C, the temperature is kept for 20 minutes to melt the pure Mg and react completely with the alloy melt; after the heat preservation is completed, the furnace is opened to remove the slag, and then the melt is refined twice; then, argon is introduced through a graphite tube, and the slag is removed again after degassing for 1 minute, and the covering agent is sprinkled on the surface of the melt. After the furnace temperature is stabilized at 740°C, the temperature is adjusted to 730°C, and after the furnace temperature is stabilized, the temperature is kept for 10 minutes, and then argon is introduced for degassing for 5 minutes;
[0019] The fourth step is to add metallic lithium: after the furnace temperature stabilizes at 730°C, fix the prepared pure lithium on the bottom of the graphite bell jar with aluminum foil, extend the graphite bell jar into the melt after the furnace is opened, and rotate it continuously to make the metallic lithium completely melt into the melt, and after the metallic lithium reacts completely with the melt, take out the graphite rod, and then immediately sprinkle the covering agent evenly on the surface of the melt, and keep the temperature for 5 minutes after the furnace temperature stabilizes at 730°C; then open the furnace to remove the slag, refine twice, introduce argon gas for degassing for 1 minute, sprinkle the covering agent on the surface of the melt again, and keep the temperature for 10 minutes after the furnace temperature returns to 730°C and stabilizes;
[0020] The fifth step is casting: the temperature of the pit-type resistance furnace is lowered to 720°C, and kept warm for 10 minutes after stabilization. In order to keep the melt warm under the protection of the argon atmosphere, argon is introduced into the melt at the same time; finally, the casting is completed under the protection of the argon atmosphere.
[0021] It is further defined that the annealing temperature in (2) is 500°C and the annealing time is 24h.
[0022] It is further defined that: (2) the annealing treatment is followed by furnace cooling.
[0023] It is further defined that (2) the thickness of the aluminum-lithium alloy plate is 20 mm.
[0024] It is further defined that the cross directions of the multiple-pass cross hot rolling treatment in (3) are RD and TD, respectively, and the cross period is each pass.
[0025] It is further defined that the temperature in the multi-pass cross hot rolling treatment in (3) is 450°C to 550°C, the reduction amount in each pass is the same, and the holding time in each pass is 5 minutes.
[0026] It is further defined that the cumulative deformation of the multiple cross hot rolling processes in (3) is 90%.
[0027] Further defined, the covering agent is a mixture of potassium chloride and calcium chloride
[0028] Further defined, the refining agent is a mixture of calcium fluoride and sodium fluoride
[0029] A third object of the present invention is to provide an application of the above-mentioned low anisotropy aluminum-lithium alloy, specifically as a lightweight and high-strength aluminum-lithium alloy.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The present invention controls the precipitation of the second phase in the matrix by reasonably adjusting the alloy elements and their contents, so that the main precipitated phases are the δ′ phase that reduces anisotropy and the Al3 (Er, Zr) composite phase, so that the obtained aluminum-lithium alloy has low density, high specific strength, high toughness and low anisotropy.
[0032] (2) The present invention regulates the texture type in the aluminum-lithium alloy by cross-rolling, eliminates the strong texture, and generates anisotropic brass-like texture {011} <111> The texture transforms into the brass R-type texture {111} which suppresses the anisotropy of the alloy <112> , further reducing the anisotropy of the aluminum-lithium alloy, reducing the alloy strength IPA from 10.1% of unidirectional rolling to 5.5%, and its elongation IPA from 12.8% to 3.3%, thereby improving the comprehensive mechanical properties of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 TEM dark field phase and selected electron diffraction spot pattern of the Al-3Li-1Cu-0.4Mg-0.1Er-0.1Zr alloy prepared in Example 1;
[0034] Figure 2 The cross-rolled {100} plane pole figure of the Al-3Li-1Cu-0.4Mg-0.1Er-0.1Zr alloy prepared in Example 1;
[0035] Figure 3 This is the cross-rolling ODF diagram of the Al-3Li-1Cu-0.4Mg-0.1Er-0.1Zr alloy prepared in Example 1;
[0036] Figure 4 The stress-strain curves of Al-3Li-1Cu-0.4Mg-0.1Er-0.1Zr alloys after being treated by different rolling processes in different embodiments and comparative examples;
[0037] Figure 5 This is a statistical chart of the IPA values of Al-3Li-1Cu-0.4Mg-0.1Er-0.1Zr alloy under different rolling processes. DETAILED DESCRIPTION
[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0039] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0040] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0041] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0042] Example 1
[0043] The aluminum-lithium alloy prepared in this embodiment is composed of the following components in mass percentage: Li 3%, Cu 1%, Mg 0.4%, Er 0.1%, Zr 0.1%, and the balance is Al, abbreviated as Al-3Li-1Cu-0.4Mg-0.1Er-0.1Zr.
[0044] The process steps for preparing the Al-3Li-1Cu-0.4Mg-0.1Er-0.1Zr alloy in this embodiment are as follows:
[0045] (1) Melting and casting
[0046] The first step is to melt the aluminum ingot: heat the pit-type resistance furnace with the crucible to 780°C, then put the pure aluminum ingot into the crucible and heat it. After the furnace temperature stabilizes at 780°C, keep it warm for 1 hour to ensure that the pure aluminum ingot is completely melted;
[0047] The second step is to add the master alloy: after the furnace is opened, the slag is firstly removed, and then the prepared Al-50wt.%Cu, Al-10wt.%Er and Al-10wt.%Zr master alloys are put into a graphite crucible, and then a small amount of covering agent (a mixture of potassium chloride and calcium chloride) is evenly sprinkled on the surface of the melt until the surface of the melt is completely covered; then the furnace temperature is returned to 780°C and stabilized, and then the temperature is kept for 40 minutes to make the master alloy completely melted and fully react with the melt. After the insulation is completed, the melt is refined twice with a refining agent (a mixture of calcium fluoride and sodium fluoride), and the slag is removed; then argon gas is introduced into the melt for 1 minute to remove impurity gases in the melt, and then the slag is removed again and a small amount of covering agent is evenly sprinkled on the surface of the melt. After the complete coverage, the furnace temperature is stabilized at 780°C and the temperature is kept for 5 minutes;
[0048] The third step is to add pure Mg: after the heat preservation is completed, the temperature is lowered to 740°C, and after the temperature is stable, the temperature is kept for 5 minutes; after the heat preservation is completed, the furnace is opened to remove the slag, and then the pure Mg is placed in the graphite crucible, and the surface of the melt is immediately covered with a covering agent, and then after the temperature is stabilized at 740°C, the temperature is kept for 20 minutes to melt the pure Mg and react completely with the alloy melt; after the heat preservation is completed, the furnace is opened to remove the slag, and then the melt is refined twice; then, argon is introduced through a graphite tube, and the slag is removed again after degassing for 1 minute, and the covering agent is sprinkled on the surface of the melt. After the furnace temperature is stabilized at 740°C, the temperature is adjusted to 730°C, and after the furnace temperature is stabilized, the temperature is kept for 10 minutes, and then argon is introduced for degassing for 5 minutes;
[0049] The fourth step is to add metallic lithium: after the furnace temperature stabilizes at 730°C, fix the prepared pure lithium on the bottom of the graphite bell jar with aluminum foil, extend the graphite bell jar into the melt after the furnace is opened, and rotate it continuously to make the metallic lithium completely melt into the melt, and after the metallic lithium reacts completely with the melt, take out the graphite rod, and then immediately sprinkle the covering agent evenly on the surface of the melt, and keep the temperature for 5 minutes after the furnace temperature stabilizes at 730°C; then open the furnace to remove the slag, refine twice, introduce argon gas for degassing for 1 minute, sprinkle the covering agent on the surface of the melt again, and keep the temperature for 10 minutes after the furnace temperature returns to 730°C and stabilizes;
[0050] The fifth step is casting: the temperature of the pit-type resistance furnace is lowered to 720°C, and kept warm for 10 minutes after stabilization. In order to keep the melt warm under the protection of the argon atmosphere, argon is introduced into the melt at the same time; finally, the casting is completed under the protection of the argon atmosphere.
[0051] (2) Homogenization annealing treatment
[0052] The cast aluminum-lithium alloy was subjected to homogenization annealing treatment at a temperature of 500°C for 24 hours. After the insulation was completed, it was cooled in the furnace to obtain an Al-3Li-1Cu-0.4Mg-0.1Er-0.1Zr alloy.
[0053] The structure of the Al-3Li-1Cu-0.4Mg-0.1Er-0.1Zr alloy was characterized. Figure 1 As shown by Figure 1 It can be seen that Figure 1 The fine and dispersed bright white second phase in a is the AL3Li phase with L12 type crystal structure. Figure 1 b shows the selected area electron diffraction spots of this phase.
[0054] The Al-3Li-1Cu-0.4Mg-0.1Er-0.1Zr alloy prepared in this embodiment is deformed: the aluminum-lithium alloy plate is subjected to multiple cross-hot rolling, and the cross directions of the cross-hot rolling treatment are RD and TD (the initial rolling direction is RD, and the other rolling direction is 90° to the initial rolling, that is, the TD direction), the cross cycle is each pass, the hot rolling temperature is 450°C to 550°C, the reduction per pass is 1mm, and the insulation per pass is 5min. Finally, the alloy is rolled to 2mm, the deformation is 90%, and the obtained Al-3Li-1Cu-0.4Mg-0.1Er-0.1Zr alloy is referred to as Cross crolling.
[0055] Comparative Example 1
[0056] The difference between this comparative example and Example 1 is that the deformation process of the Al-3Li-1Cu-0.4Mg-0.1Er-0.1Zr alloy is to perform multiple hot rolling on the aluminum-lithium alloy plate, the hot rolling direction is RD, the hot rolling temperature is 450℃~550℃, the reduction amount is 1mm per pass, and the heat preservation time is 5min per pass. Finally, the alloy is rolled to 2mm, the deformation amount is 90%, and the obtained Al-3Li-1Cu-0.4Mg-0.1Er-0.1Zr alloy is referred to as Normal crolling. The rest of the operation process and parameter settings are the same as those in Example 1.
[0057] The texture structure of Al-3Li-1Cu-0.4Mg-0.1Er-0.1Zr alloy after deformation by two hot rolling methods was characterized. Figure 2 and Figure 3As shown in Figure 2, the analysis shows that the unidirectional rolled aluminum-lithium alloy mainly contains brass-like texture {011} <111> orientation, while cross-rolling mainly contains brass R-type texture {111} <112> orientation, it can be found that cross-rolling changes the texture composition of the alloy after unidirectional rolling. The brass R-type texture {111} <112> The strength has been improved and the brass-like texture has been eliminated {011} <111> At the same time, a faint cubic texture {001} <100> The main texture of the alloy is brass-like texture {011} <111> Transformed to brass R-texture {111} <112> The mechanical properties of the Al-3Li-1Cu-0.4Mg-0.1Er-0.1Zr alloys after deformation treatment in Example 1 and Comparative Example 1 were characterized. The stress-strain curves are shown in Figure 4 As shown by Figure 4 It can be seen that the six tensile curves are sampled at 0°, 45°, and 90° to the RD direction for two rolling methods. It can be seen that the tensile strength of the unidirectional rolled alloy in each direction is quite different, among which the tensile strength in the RD direction is the highest, which can reach 362MPa, and the tensile strength in the TD direction of the alloy is the lowest, which is only 306MPa. The average strength of the unidirectional rolled aluminum-lithium alloy is 338MPa. At the same time, it can be seen that the tensile strength of the cross-rolled aluminum-lithium alloy in each direction is relatively small, among which the tensile strength in the RD direction is still the highest, which can reach 342MPa. The tensile strength of the alloy in the 45° direction is the smallest, which is 319MPa. After cross-rolling, the average strength of the alloy decreases slightly to 329MPa, which is 9MPa lower than that of unidirectional rolling. Overall, among the tensile strengths of all specimens, the strength in the RD direction of the unidirectional rolled state is the highest, and the strength in the TD direction of the unidirectional rolled state is the lowest. It can be seen that the strength of the unidirectional rolled alloy in each direction is quite different.
[0058] IPA value statistics of different rolling processes, such as Figure 5 As shown by Figure 5 It can be seen that after cross-rolling, the strength IPA index of the aluminum-lithium alloy is reduced from the original 10.1% to 5.5%, and its elongation IPA index is also reduced from 12.8% to 3.3%, indicating that the anisotropy of the aluminum-lithium alloy is significantly improved after cross-rolling.
[0059] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A low anisotropic aluminum-lithium alloy, characterized in that: The aluminum-lithium alloy consists of the following components in mass percentage: Composition: Li 3%, Cu 1%, Mg 0.4%, Er 0.1%, Zr 0.1%, and the balance is Al.
2. The low anisotropic aluminum-lithium alloy according to claim 1, characterized in that: The precipitated phases of the aluminum-lithium alloy are mainly δ′ phase and Al3 (Er, Zr) composite phase.
3. The low anisotropic aluminum-lithium alloy according to claim 1, characterized in that: The aluminum-lithium alloy is obtained by smelting and casting aluminum ingots, Mg, metal lithium, intermediate alloys Al-50wt.% Cu, Al-10wt.% Er and Al-10wt.% Zr as raw materials to obtain a cast alloy, and then annealing and plate rolling treatment.
4. A method for preparing the low anisotropic aluminum-lithium alloy according to any one of claims 1 to 4, characterized in that: include: (1) melting and casting to obtain a cast AlLiCuMgErZr alloy; (2) annealing the cast AlLiCuMgErZr alloy, and then cutting it to obtain an aluminum-lithium alloy plate; (3) The aluminum-lithium alloy plate is subjected to multiple cross hot rolling, with the cumulative deformation being greater than 70% and the hot rolling temperature being 450° C. to 550° C.
5. The method for preparing the low anisotropic aluminum-lithium alloy according to claim 4, characterized in that: (1) The melting temperature is 730℃~780℃.
6. The method for preparing the low anisotropic aluminum-lithium alloy according to claim 4, characterized in that: (2) The annealing temperature is 500°C and the time is 24h.
7. The method for preparing the low anisotropic aluminum-lithium alloy according to claim 4, characterized in that: In (3), the cross directions of the multi-pass cross hot rolling treatment are RD and TD, and the cross cycle is each pass.
8. The method for preparing the low anisotropic aluminum-lithium alloy according to claim 4, characterized in that: (3) The temperature in the multi-pass cross hot rolling process is 450℃-550℃, the reduction amount in each pass is the same, and the holding time in each pass is 5min.
9. The method for preparing the low anisotropic aluminum-lithium alloy according to claim 4, characterized in that: (3) The cumulative deformation of the multi-pass cross hot rolling process is 90%.
10. Use of the low anisotropic aluminum-lithium alloy according to claim 1 as a light-weight and high-strength aluminum-lithium alloy.